Impact of Transformational leadership on nurse’s teamwork patients and family members - A systematic Review - Laltanpuii, Linda; Sharma, Poonam (Journal of Neonatal Surgery, 2025)
The healthcare industry has been constantly developing, with an increasing necessity to advance care for patient while also accurately addressing the satisfaction and well-being of healthcare professionals, specifically nurses. Nurses play an important role within healthcare system, as they are often the main point of connection for affected people. Their satisfaction of job, different team works, and appointment directly impact the value of attention they deliver and the overall competence and presentation of overall healthcare settings. In recent years, there has been almost a growing attention within the leadership style’s role in accurately shaping the environment of workplace particularly within healthcare. Among the different approaches of leadership, transformational leadership has got extensive care for its possibility to enhance many positive outcomes in several nursing teams. This leadership style has been categorized by the overall capability to both inspire and also stimulate many team members to accurately gain common goals, inspire personal development, and also build a supportive as well as innovative workplace. Research has also shown that many transformational leaders are able to enhance communication and teamwork, and also even collaboration among many nurses. Through empowering many nurses and also by encouraging their involvement within the process of decision-making processes, many transformational leaders are able in accurately contributing to a huge level job satisfaction and also a better job retention. Additionally, a motivated and also cohesive nursing team is also better equipped to give good quality care, ensuring enhance patient outcomes. Even the presence of the amplified indication that is further supporting the benefits of transformational leadership, there also stays a need for a clear and deep empathetic of how this style of leadership specifically influences nursing teamwork, satisfaction of jobs, and also the good quality of care in various healthcare settings. This particular study mainly aims to reveal the overall influence of transformational management on all these key factors, with the main goal of providing effective recommendations for many healthcare organizations seeking to improve nursing performance and patient care outcomes. transformational behaviors play a significant role in declining operate business, which may additional also indirectly suggest the presence of task gratification of nurses as a significant facilitating influence (Abdelhafiz et al., 2016; Abualrub & Alghamdi, 2012). At the same time, a number of transformational nurse privileged can also identify and then anticipate the requirements of their staff nurses that is through building almost a strong relationship and also by making numerous considerable efforts in order to meet their needs, which further significant in fostering a strong sense of authorization and also independence that can also ultimately lead to increase level of work satisfaction (Asif et al., 2019). At the same time, several related educations have also deduced that the empowered management style can directly contributes to the reduction of nurses’ revenue (Magbity et al., 2020; Pishgooie et al., 2019). Result: In conclusion, the style of particular leadership that is transformational can accurately enhance job satisfaction, which, in turn, can further improve the overall well-being of the nurses' overall and also the effectiveness within their roles. Empowered leadership has almost an important and very positive impact on various nursing teams. It is also influencing teamwork, level of job approval, and also the overall good quality of patient care. This leadership style also encourages nurses to be very motivated, almost inspired, and very supported within their roles, which ultimately fosters a strong sense of empowerment and also increases overall engagement. Through accurately adopting transformational leadership, many healthcare leaders are able in promoting collaboration, effective communication, and also a shared vision that is among nursing staff, which further enhances teamwork. When nurses feel both valued and supported then ultimately their job satisfaction automatically improves. It further leading to decreased rates of burnout and also increased retention. A satisfied and also a motivated workforce is very essential for accurately delivering good and high-quality care to many patients, further ensuring patient outcomes and satisfaction that is for patient. Healthcare firms that accurately embrace transformational leadership create almost a significant environment conducive to professional growth, a very strong team dynamics, and enhance patient care. Due to this, it is also suggested that multiple health care settings prioritize leadership that is transformational in order to optimize both satisfaction for nursing job and also the good quality of care that is provided to patients.